Linguistic Discrimination꞉ A cross-cultural study of experiences of non-majority language speakers in Slovakia and Spain - Ewelina Urbanska; Martin Plachetka (Teanga: The Journal of the Irish Association for Applied Linguistics)
Non-majority languages are undeniably part of every culture. Those who belong to a non-majority language group are often subjected to sidelining in various areas of life, e.g., education system, labour market or social settings. This qualitative study outlines the extent of linguistic discrimination and its impact on the speakers of non-majority languages. It explicitly concentrates on two non-majority language groups, i.e., Romani language speakers in Slovakia and English speakers in Spain. Two very distinct groups are purposely chosen to emphasise the omnipresent existence of linguistic discrimination and its effect on the speakers of the non-majority language members of society. Findings highlight that both groups experience similar levels of discrimination across multiple settings and that the discrimination faced often intersects with race and ethnicity.